2016
DOI: 10.3109/14767058.2016.1149560
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different information sources on the anxiety level of pregnant women who underwent invasive prenatal testing

Abstract: Doctors and nurses should allocate enough time for providing information about prenatal diagnosis before the procedure. This will reduce the anxiety level as well as the felt necessity to search for information from other sources, such as personal or popular which will further increase the level of anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
2
15
0
1
Order By: Relevance
“…Çakar et al, identified the fear of receiving bad news as a main factor why patients feel anxious before an invasive procedure. Moreover, they found that patients who had received information from doctors or nurses had lower anxiety levels compared to patients who had either received no information or information from friends and family [30]. The fact that NIPT is only available in a controlled medical environment (and not for sale on the internet) might help to assure good quality counseling and reduce patients’ anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Çakar et al, identified the fear of receiving bad news as a main factor why patients feel anxious before an invasive procedure. Moreover, they found that patients who had received information from doctors or nurses had lower anxiety levels compared to patients who had either received no information or information from friends and family [30]. The fact that NIPT is only available in a controlled medical environment (and not for sale on the internet) might help to assure good quality counseling and reduce patients’ anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…6 Çakar'ın yaptığı çalışmada, gebelerin yaş ortalamasının 32 yıl olduğu saptanmıştır. 13 Son yıllarda annelik yaşının; kadınların çalışmaya hayatına girmesi, kariyer planlaması ve üremeye yardımcı tekniklerin gelişmesi gibi nedenlerle gebeliğin yaşamın ilerleyen dönemine ertelendiği yaygın bir şekilde görülmektedir. Sonuç olarak annelik yaşı gün geçtikçe artmaktadır.…”
Section: Discussionunclassified
“…Younger women may be seen as emotionally immature (Bhattacharjee, 2016), and low educational attainment is related to precarious work with variable shifts among women (Schieman & Glavin, 2011). Low monthly incomes strain economic resources given the effects of increasing housing prices (Li & Wu, 2018) and costs to raise newborns (Buddelmeyer, Hamermesh, & Wooden, 2018). Women with short marital durations may be unsatisfied with their marital relationships (Abe & Oshio, 2018).…”
Section: Conflicts With Mothers-in-lawmentioning
confidence: 99%